EVALUASI STRATEGI PEMASARAN PADA MASA PANDEMI COVID19 - harry ramadhan; endah widati; ibnu fiqhan muslim (VALUE, 2021)
Competition in the restaurant and cafe industry at this time is very tight and competitive. This is marked by the growing number of new competitors in the world of Resto and Cafe. The restaurant and cafe industry as one of the food and beverage supply sectors that can support national and regional economic development. In Depok, there are 170 restaurants and cafes operating. The purpose of this study was to find out how the results of the implementation of Marketing Strategy During the Covid19 Pandemic at Like No Other Cafe Depok. The research method used is descriptive qualitative method. Using interviews, questionnaires and observations to related parties as data collection techniques. Thus, the data analysis techniques used were VRIO and PESTLE analysis to analyze the business environment, profitability analysis to evaluate the results of the implementation of the marketing mix program used and descriptive analysis to analyze planning, implementation and marketing strategy activities. The results showed that the strategy implemented by Like No Other Cafe during the Covid19 pandemic was considered effective so that Like No Other Cafe was still able to survive and generate income even though the income was only 50% of normal conditions.